1993
DOI: 10.1177/00220345930720110501
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Distribution of Human PMN Elastase and Cathepsin-G in Dental Pulp

Abstract: Components of primary (azurophilic) granules of polymorphonuclear leukocytes (PMNs) have been implicated as important mediators in pulpal inflammation. This anatomical study used ultracryoimmunocytochemical techniques and characterized and contrasted the subcellular distributions of human PMN elastase (PMN-E), PMN cathepsin-G (PMN-CG), and alpha-2 macroglobulin (alpha-2M) in healthy and inflamed dental pulps. Inflamed pulpal tissue sections revealed an intense distribution of PMN-E in the extracellular domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Increased levels of several proteolytic enzymes such as elastase, cathepsin G, and MMP-8 released by PMNs in pulpitis and chronic apical periodontitis have been reported (9,10). In this study, TNF-a, IL-1a, and MMP-8 were clearly up-regulated when PMNs were incubated with E. faecalis in vitro (Fig.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Increased levels of several proteolytic enzymes such as elastase, cathepsin G, and MMP-8 released by PMNs in pulpitis and chronic apical periodontitis have been reported (9,10). In this study, TNF-a, IL-1a, and MMP-8 were clearly up-regulated when PMNs were incubated with E. faecalis in vitro (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Polymorphonuclear neutrophils (PMNs) are in general regarded as the most efficient first line of defense cells against invading microorganisms. PMNs play an important role in the early control of acute bacterial infections by killing bacterial pathogens through powerful oxidative and nonoxidative mechanisms and through the production of inflammatory and immunoregulatory cytokines and chemokines, such as tumor necrosis factor a (TNF-a), interleukin-1 (IL-1), and proteolytic enzyme, such as matrix metalloproteinases-8 (MMP-8, neutrophil collagenase) (8)(9)(10). These molecules lead to the influx and activation of PMNs and macrophages at the site of infection, which are important first steps in the development of inflammation (11).…”
mentioning
confidence: 99%
“…A positive relationship exists between pulpitis and the increase of neutrophil elastase activity in humans (23). Polymorphonuclear leukocyte elastase was observed in the periapical tissue of patients clinically diagnosed as having irreversible pulpitis (24). Neutrophil elastase is detected in the periodontal ligament of patients with periodontitis (33).…”
Section: Discussionmentioning
confidence: 99%
“…This protease has wide substrate specificity and has strong competency in degrading a variety of the proteins including elastin (22). There is a possibility that it evokes the severe tissue destruction seen in pulpitis (23) and periradicular lesions (24). In human periapical disease, neutrophil elastase levels of periapical exudates associated with clinical symptoms (25) and there may be a possibility that it serves as a diagnostic marker (26).…”
mentioning
confidence: 99%
“…Studies on entire pulp tissue consistently showed that PMN‐related enzymes such as elastase and cathepsin G and MMP‐9 are elevated in clinically inflamed pulps compared to healthy dental pulps. Histologically, the presence of these enzymes or their respective mRNAs is strongly correlated to the inflammatory infiltrate . The same is true for IL‐8, the main neutrophil chemoattractant.…”
Section: Which Target Molecules Should Be Considered?mentioning
confidence: 99%